Parental protein malnutrition programmes of offspring growth and vasculature to increase risk of cardiovascular, pancreatic, and metabolic disease: lessons learned from animal studies - Ruiz-Diaz, Maria Dolores; Partridge, Hannah; Davidson, Francesca; Mongan, Nigel P.; Gardner, David S.; Rutland, Catrin S. (European Medical Group Ltd, 2017)
It is well known that consumption of a balanced diet throughout adulthood is key toward maintenance of optimal body weight and cardiovascular health. Research using animal models can provide insights into the programming of short and long-term health by parental diet and potential mechanisms by which, for example, protein intake may influence fetal development, adolescent health, and adult morbidity/mortality. Malnutrition, whether consumption of too many or too few individual nutrients or energy, is detrimental to health. For example, in Westernised societies, one of the principal factors contributing towards the global epidemic of obesity is over-consumption of calories, relative to the expenditure of calories through physical activity. A large body of evidence now suggests that many chronic diseases of adulthood, such as obesity and diabetes, are linked to the nutritional environment experienced by the fetus in utero. Maternal consumption of a poor-quality, nutritionally unbalanced diet can programme offspring to become obese, develop high blood pressure and diabetes, and to experience premature morbidity and mortality. More recently, paternal diet has also been shown to influence offspring health through effects carried via the sperm that affect post-fertilisation development. Mechanisms underpinning such developmental programming effects remain elusive, although early development of the microvasculature in the heart and pancreas, particularly after exposure of the mother (or father) to a protein restricted diet, has been proposed as one mechanism linking early diet to perturbed adult function. In this brief review, we explore the longer-term consequences of maternal and paternal protein intakes on the progeny. Using evidence from relevant animal models, we illustrate how protein malnutrition may ‘programme’ lifelong health and disease outcomes, especially in relation to pancreatic function and insulin resistance, and cardiac abnormalities.